2010
DOI: 10.1016/j.tsf.2009.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Use of p- and n-type vapor phase doping and sub-melt laser anneal for extension junctions in sub-32 nm CMOS technology

Abstract: We evaluated the combination of vapor phase doping and sub-melt laser anneal as a novel doping strategy for the fabrication of source and drain extension junctions in sub-32 nm CMOS technology, aiming at both planar and non-planar device applications. High quality ultra shallow junctions with abrupt profiles in Si substrates were demonstrated on 300 mm Si substrates. The excellent results obtained for the sheet resistance and the junction depth with boron allowed us to fulfill the requirements for the 32 nm as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…However, the junction depths are quite deep highlighting the need for more advanced annealing techniques with faster ramp up and ramp down rates in addition to emerging techniques such as flashlamp and laser annealing. 5154…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the junction depths are quite deep highlighting the need for more advanced annealing techniques with faster ramp up and ramp down rates in addition to emerging techniques such as flashlamp and laser annealing. 5154…”
Section: Resultsmentioning
confidence: 99%
“…Despite the difficulty in characterizing the Si-doped samples, we have shown that it is possible to co-dope InGaAs with S and Si simultaneously using liquid-phase, ambient pressure surface chemistry. However, the junction depths are quite deep highlighting the need for more advanced annealing techniques with faster ramp up and ramp down rates in addition to emerging techniques such as flashlamp and laser annealing. …”
Section: Resultsmentioning
confidence: 99%
“…Classical standard doping techniques like ion implantation may not be suitable for FinFET devices because of the 3D geometry. Several solutions to incorporate dopants in the fin are being explored such as tilted ion implantation [23,153,158], plasma doping [159][160][161][162] or vapor phase doping [163]. Among them, tilted ion implantation remains a strong candidate to introduce dopants into the fin, as it is a conventional and well established technique, although it suffers from specific issues that arise from the particular geometry of these devices.…”
Section: Doping Issues In Finfet Devices: a Challenge In 3dmentioning
confidence: 99%
“…Vapor-phase doping technique is utilized to achieve the p and n δ-doping spike, wherein the dopant atoms are deposited on the wafer by thermal decomposition of diborane (B 2 H 6 ) and phosphine (PH 3 ), respectively [24], [25]. A set of four wafers were grown with the boron flow varied over a factor of 6 to modify the boron content in the bottom δ-doped layer.…”
Section: Epitaxy (Mbe) At 370mentioning
confidence: 99%